If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13 + -2x) * 4 + -2x = 16 Reorder the terms for easier multiplication: 4(13 + -2x) + -2x = 16 (13 * 4 + -2x * 4) + -2x = 16 (52 + -8x) + -2x = 16 Combine like terms: -8x + -2x = -10x 52 + -10x = 16 Solving 52 + -10x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + -10x = 16 + -52 Combine like terms: 52 + -52 = 0 0 + -10x = 16 + -52 -10x = 16 + -52 Combine like terms: 16 + -52 = -36 -10x = -36 Divide each side by '-10'. x = 3.6 Simplifying x = 3.6
| z=2(z-12) | | s+11=2s | | z=2(z-32) | | 16x^2-9=91 | | 2x+50=3y | | (8-4x)3+2x=-108 | | z-7=2z-31 | | (w-2)2= | | 4(3)+3(y)=6 | | 9(12n-6)=15(7n) | | 4(3)+3y=6 | | 2x^2-4x=19 | | (7-3x)3-7x=1 | | x*a=287 | | (2+3x)2+-5x=13 | | a*b=287 | | w=2w-49 | | 4(5x+1)-2(3x-4)=12x+36 | | w=w-40 | | Cot^2(3x)=1 | | 3x^5=-3 | | 49w^2+35w+6=0 | | X=8/3x-16 | | 10c+14=1-4 | | -3(v+1)=-8v-13 | | −17=v/2 | | b-14=5 | | 11x+7y=-28 | | 4x-7/x=3 | | 2(4x+25)=200-4x | | 3/2*-5/2=19/2 | | 7.5(40+n)+11.25n=339.38 |